The Study of Jewish Christianity - Klijn, Albertus Frederik Johannes (New Testament studies, 1974)
In 1830 F. C. Baur tried to demonstrate that the early Church was split up into Jewish Christians and Gentile Christians, but more than a hundred years later H. Köster wrote: ‘…a label such as, for example, “Jewish-Christians” is misleading insofar as everyone in the first generation of Christianity was a Jewish-Christian anyway…’. In spite of this observation it still seemed possible to organize a ‘colloque’ on Jewish Christianity and to publish a book with many contributions to this subject. But it cannot be denied that the word ‘Jewish Christian’ poses a problem which we shall study in the present essay. First we shall give a brief survey of the study of Jewish Christianity from F. C. Baur to the present time in order to show the development of the word ‘Jewish Christian’, and with the results of this survey we shall then try to show what can be regarded as belonging to the field of Jewish Christianity at the present moment.